Ofloxacin/Ornidazole Induced Toxic Epidermal Necrolysis: Case Report - Inamdar, Syed Zia; Swapna, Chirasini; Kumar, Pavan; Londhe, Sushilkumar; Bentoor, Sanjeev; Janagond, Ajith; Raikar, Shrinivas (Indian Journal of Pharmacy Practice)
Toxic Epidermal Necrolysis (TEN) is a rare, life-threatening mucocutaneous disorder, most often triggered by medications and less frequently by infections. It is clinically characterized by widespread erythema, epidermal necrosis, and extensive bullous detachment of the skin and mucous membranes, which may progress to exfoliation, sepsis, and even death. Drugs commonly associated with TEN include sulfonamides, non-steroidal anti-inflammatory agents, imidazole antifungals, cephalosporin’s, anticonvulsants, and allopurinol. We report the case of a patient admitted to a tertiary care center with painful, fluid-filled skin lesions involving the trunk and extremities. Medical history revealed intake of Ofloxacin with Ornidazole for chest pain and breast swelling. Based on clinical features, history, and causality assessment, Ofloxacin/ Ornidazole was identified as the most likely culprit. The drug was discontinued and symptomatic management initiated.
Keywords: Adverse Drug Reaction; Ofloxacin; Severe Cutaneous Adverse Reaction (SCAR); Skin; Lesions; Toxic Epidermal Necrolysis